Mendesain Ulang Organisasi Pelayanan Publik Melalui Digitalisasi Proses Bisnis - Denok Kurniasih; Anggara Setya Saputra (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2017)
This study aims to analyze the design changes of public service organizations by taking cases on licensing service organizations in Banyumas Regency. The results show that merging and pruning organizational structure becomes the only way in organizational design changes. This has led to public service organizations stuck on simplifying organizational structures and neglecting business processes. Therefore, through this research obtained an explanation of the importance of redesigning public service organizations by prioritizing the simplification of key business processes within the organization. The integrated organizational design becomes the best choice to realize more responsive and accountable public services. To integrate the process of integration between units within the organization, technology plays a very important role. Any organization that wants to go forward needs to develop a digital-based organization design rather than using a hierarchical mechanism for control and coordination. Such designs require strategic alignment and the culture of digital technology within the organization. The